Salmonella typhimurium infection in calves: protection and survival of virulent challenge bacteria after immunization with live or inactivated vaccines. - Robertsson, J A (1983)
Salmonella typhimurium SL1479, an auxotrophic mutant strain having a complete block in the aromatic biosynthetic pathway and therefore requiring p-aminobenzoic acid and 2,3-dihydroxybenzoate not available in mammalian tissues, was given orally in a dose of 10(10) live bacteria to 4- to 5-week-old calves. Only a mild transient fever response was seen. Strain SL1479 was unable to colonize and persist in the calves for more than 2 weeks. In a vaccination experiment, groups of six calves were (i) orally vaccinated with the live S. typhimurium SL1479 strain, (ii) subcutaneously vaccinated with a heat-inactivated S. typhimurium SVA1232 strain with aluminum hydroxide as adjuvant, or (iii) not vaccinated, to serve as controls. Calves were orally challenged with the live, calf-virulent S. typhimurium SVA44 strain: either 10(6) bacteria (equivalent to 100 25% lethal doses [LD25S]) or 10(9) bacteria (100,000 LD25S doses). The live oral vaccine gave significantly better protection than the heat-vaccinated, subcutaneously injected vaccine since (i) only control calves and calves given the killed vaccine developed profuse diarrhea, (ii) clinically, the mild fever responses seen after challenge in calves given the live vaccine were significantly lower (P less than 0.0005), (iii) autopsies performed 21 days after the challenge infection revealed normal findings in calves given the live vaccine, whereas calves given the killed vaccine showed signs of acute enteritis and chronic salmonellosis, (iv) all 12 calves given either 100 X or 100,000 X the LD25 survived the 21-day observation period; the mean survival time in nonvaccinated calves was 8.0 days; in calves given heat-inactivated vaccine and 100 X the LD25 it was 21.0 days, and in calves given 100,000 X the LD25 it was 11.5 days, (v) the fecal bacterial counts of the challenge S. typhimurium SVA44 strain were significantly lower (P less than 0.0005) in both groups given the live vaccine, and (vi) upon autopsy followed by culture, the qualitative recovery of the challenge strain from the alimentary canals and tissues of calves given the live vaccine was significantly lower (P less than 0.005).